Inventory Control in a Fluctuating Demand Environment - Song, Jing-Sheng; Zipkin, Paul (Operations Research, 1993)
We present an inventory model, where the demand rate varies with an underlying state-of-the-world variable. This variable can represent economic fluctuations, or stages in the product life-cycle, for example. We derive some basic characteristics of optimal policies and develop algorithms for computing them. In addition, we show that certain monotonicity patterns in the problem data are reflected in the optimal policies.